Mathematical modeling and forecasting of esophageal and stomach cancer case rate in Kazakhstan - Galiya Orazova; Leonid Karp; Gulnar Rakhimbekova; Anargul Nogayeva (National Scientific Medical Center, 2016)
Objective. Create a mathematical model and forecast esophageal and stomach cancer case rate in Kazakhstan up to the year 2020. Methods: It is retrospective, descriptive-analytical study. Primary information sources during performance of this work were indicators of oncological service of the Republic of Kazakhstan for 1990-2014. Forecasting on the level of esophageal and stomach cancer case rate was performed through the development of time-series model and their extrapolation. The length of the forecast period was identified by the length of actual data series. Total forecast in the country up to the year 2020 was made on the basis of data for 1990-2014. Unfortunately, due to the insufficiency of data in archives, we failed to obtain the required volume of data across the country regions for the specified period. Comparatively short regional database, which covers the period from 1999 to 2014, allowed to extrapolate the obtained models for 2-3 years in advance, in our case - up to 2017. Considering the dynamics peculiarities of esophageal and stomach cancer case rate among the country population, the most relevant method for forecasting is the logarithmic function. Results. According to the results of forecasting, there was some tendency to the growth of esophageal and stomach cancer case rate among the population of Akmola (from 8,900/0000 to 9,650/0000), Almaty (from 5,740/0000 to 6,130/0000) and Kostanay (from 9,450/0000 to 10,590/0000) regions. Based on the forecast of stomach cancer case rate in Zhambyl region, there is a possibility of the growth from 15,00/0000 to 16,00/0000 till the year 2017. In all other regions there was a common tendency to stabilization and decrease in stomach cancer case rate. Nationwide, there is a tendency to the decrease in esophageal cancer (7,90/0000) and stomach cancer (17,00/0000) case rate to the year 2020. Conclusion. In connection with the identification of esophageal and stomach cancer case rate growth in a certain regions of Kazakhstan during mathematical forecasting, there is a viability of further investigations on the detailed study of possible cause and effect relationships of this phenomenon.